Primary Tooth Extraction Pattern Among Turkish Children with Severe Early Childhood Caries Treated Under General Anesthesia - Merve Candan; Burak Buldur (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the frequency and distribution of extracted primary teeth due to severe Early Childhood Caries (ECC) in young pediatric patients treated under general anesthesia. Material and Methods: This study employed a retrospective design and consisted of a total of 1644 children (1011 boys, 633 girls) children aged 3 to 5 who had been diagnosed with several ECC and treated under general anesthesia in a dental faculty between 2013-2019. The data was obtained from the medical and dental forms obtained from the faculty database. The patients were divided according to age groups and sex. A total of 2605 teeth were classified according to the sex, tooth number, and  age  groups. Results: Of the subjects, 14% (n = 245) were 3 years old, 31% (n = 505) were 4 years old, 55% (n = 894) were 5 years old. The mean ± SD age of subjects was 4.2 ± 0.8 yr. While the most extracted teeth were found to be maxillary primary central incisors and molar teeth, the less were found to be mandibular primary canines. While there was a statistically significant difference between canines and incisors with molars (p<0.05), no difference existed between incisors and molars. There was a statistically significance difference among all age groups (p<0.05). While 3 years old group had the less number of extracted teeth, 5 years old group had the most number of extracted teeth. Conclusion: Severe ECC causes higher tooth extraction in patients treated under general anesthesia. Effective personal and community programs should be initiated to prevent ECC and mitigate its potential disruptive impacts in children's oral health.